Method and metrological characteristics of measuring the mass fraction of monosodium glutamate in biological matrices - A. S. Knyazeva; N. L. Vostrikova; A. V. Kulikovskii; D. A. Utyanov (Пищевые системы)
Over the last century the people’s mode of life and eating habits has dramatically changed: the people of developed countries began to consume fast food, and also started disorderly and frequent snacking. The production of dietary meals and the increase of food assortment, including food produced from low-quality ingredients, led to the manufacturer’s necessity to use a large number of functional ingredients, i. e. those that improve taste of the food. Monosodium glutamate (MSG) is one of the widely used additives. Monosodium L-Glutamate (E621) is the sodium salt of glutamic acid found in all protein foods; it is used throughout the world as a food flavor enhancer. The legislation of the Russian Federation limits the content of monosodium glutamate, or additive E621, in a food product. Due to the fact that the glutamic acid takes the major weight in the monosodium glutamate molecule, which molecule is naturally present in almost all food products, the weight of the molecule of the E621 additive was determined by content of this amino acid expressed in terms of monosodium glutamate. In connection with the foregoing, it became necessary to develop a method for the quantitative determination of the mass fraction of monosodium glutamate introduced into food during the production of food products. Within the framework of this research a new method for determining the share of added monosodium glutamate is proposed, which is not associated with the natural content of glutamic acid. The authors have developed a method for determining the mass fraction of monosodium glutamate in food products with the help of high performance liquid chromatography with precolumn derivatization. This research presents metrological assessment of the developed methodology, determines accuracy rates and reproducibility factors in two concentrations ranges. For a range of 0.1 to 1%, the reproducibility is set at 17% and the accuracy rate is set at 30%. For the range of 1–10%, the reproducibility is 6%, the accuracy rate is 10% respectively. Also, during the development of the method, the lower limits for the quantitative determination (Limit of Detection — LOD) and qualitative determination (Limit of Quantification — LOQ) of the method were calculated. LOQ was equal to 0.01% and LOD accounted for 0.1%. The method has successfully passed the metrological certification and is included in the Register of Measurement Methods of the Russian Federation. It can be used by accredited laboratories for assessment and control of food quality.